Four new species of Utivarachna Kishida, 1940 (Araneae: Trachelidae) from Sumatra - Dhiya’ulhaq, Naufal Urfi; Dupérré, Nadine; Buchori, Damayanti; Scheu, Stefan; Drescher, Jochen (Zootaxa, 2024)
Four new species of trachelid spiders belonging to the genus Utivarachna Kishida, 1940 are described: U. angsoduo sp. nov., U. balonku sp. nov., U. rimba sp. nov., and U. trisula sp. nov. Part of the EFForTS project, the spider specimens were uncovered in a canopy fogging collection of tree crown arthropods along a land-use gradient from rainforest via jungle rubber (rubber agroforestry) to monocultures of rubber and oil palm in Jambi Province, Sumatra, Indonesia. Three of the proposed new species were found exclusively in rainforest or jungle rubber agroforest (U. angsoduo sp. nov., U. rimba sp. nov., U. trisula sp. nov.), and one of them exclusively in monocultures of rubber trees (U. balonku sp. nov.). We provide photographs and distribution maps for the proposed new species, and discuss their potential ecology based on their sampling locations. We also encountered a fifth species of the genus in all four land-use systems, U. phyllicola Deeleman-Reinhold, 2001, one of two species of the genus previously recorded from Sumatra, and also provide photographs and distribution maps for this species in the research area of the EFForTS project.